(untitled) (Annals of Bangladesh Agriculture, 2023)
The pool barb (Puntius sophore) is an indigenous freshwater species of Bangladesh. The population size structure, sex ratio, condition factor, gonadosomatic index, and fecundity of P. sophore were estimated as biological parameters in the present study. A total of 480 specimens were collected in 12 months from the River Brahmaputra between July 2019 and June 2020. Length-frequency data revealed that the length of the maximum number (155) of individuals in catch sample was in 9-11cm intervals. The average male: female ratio was 1.0:1.4 indicating female dominance in the population throughout the year though there was no significant difference between the sex ratio (χ2=0.34, P>0.05). Mean condition factor (K) was different in different months. Both sexes experienced the highest condition factor (K) in June, and the lowest in February and January, respectively. The GSI in both sexes fluctuated significantly in different months and showed one peak in June. Total fecundity varied from 960 to 5680 (3116±1411). The arithmetic equations of fecundity against TL, BW, and OW were F=3409.33+615.35 TL, F=462.47+40.20 BW, and F=2932.9+2839.32 OW respectively. The scatter diagram between fecundity with TL, BW, and OW demonstrated a linear relation and positive association between the three variables. The findings of this investigation offer baseline information on a few biological characteristics of P. sophore, information that will help forecast the reactions of P. sophore populations in the Old Brahmaputra River. Ann. Bangladesh Agric. (2023) 27 (2): 59-70